Earnings Inequality, Returns to Education and Immigration into Ireland - Alan Barrett; John FitzGerald; Brian Nolan (Institute for the Study of Labor (IZA), 2000)
Increasing earnings inequality has been an important feature of the US and UK labour markets in recent years. The increase appears to be related to an increased demand for skilled labour and an increase in the returns to education. In this paper we examine what has happened to earnings inequality and the returns to education in Ireland between 1987 and 1997. We find that while both increased between 1987 and 1994, the increases slowed dramatically between 1994 and 1997. This is somewhat surprising as the exceptional growth in the Irish economy occurred from 1994 on. We look to immigration as being a contributing factor to this pattern because a large group of skilled workers flowed into the Irish labour market between 1994 and 1997. We develop a model of the Irish labour market and use it to simulate the impact of an increase in skilled labour. The simulation suggests that immigration did indeed reduce earnings inequality. This result is an interesting corollary to work from the US that shows the immigration of unskilled workers increasing earnings inequality.
Keywords: J61; 330; Earnings inequality; returns to education; immigration; Ireland; Lohnstruktur; Einkommensverteilung; Bildungsertrag; Einwanderung; Internationale Arbeitsmobilität; Hochqualifizierte Arbeitskräfte; Irland